DEVELOPMENT OF A GAME FOR LEARNING LINEAR FUNCTIONS IN A REAL-WORLD CONTEXT TO IMPROVE THE CONCEPTUAL UNDERSTANDING OF JUNIOR HIGH SCHOOL STUDENTS: PENGEMBANGAN PERMAINAN UNTUK PEMBELAJARAN FUNGSI LINIER DALAM KONTEKS DUNIA NYATA UNTUK MENINGKATKAN PEMAHAMAN KONSEPTUAL SISWA SEKOLAH MENENGAH PERTAMA - Dhananjaya, Hasmara Adhi; Haryani, Faradillah (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
Linear functions in math are essential for advanced topics like calculus and physics. In Indonesia, linear function teaching is limited to whiteboard calculations or simple drawings without contextual explanations. It's crucial to emphasize factual and conceptual math knowledge for deep understanding and effective learning by bringing more contextual problems. Many teachers use traditional games or modeling activities to create contextual problems for students. However, none of them was created for the learning function in digital games. This project aims to develop a game for learning linear functions using contextual challenges. The game was created utilizing an ADDIE model. Validation is using Learning Object Review Instrument (LORI) with three different validators who have different expertise in content, technology, and classroom implementation. The data shows that this game may reinforce learning linear functions. A future research project may examine the impact of playing this game on students' conceptual understanding of linear function.